2013
DOI: 10.1038/jcbfm.2013.151
|View full text |Cite
|
Sign up to set email alerts
|

PKC-βExacerbatesin vitroBrain Barrier Damage in Hyperglycemic Settings via Regulation of RhoA/Rho-kinase/MLC2 Pathway

Abstract: Stroke patients with hyperglycemia (HG) develop higher volumes of brain edema emerging from disruption of blood-brain barrier (BBB). This study explored whether inductions of protein kinase C-b (PKC-b) and RhoA/Rho-kinase/myosin-regulatory light chain-2 (MLC2) pathway may account for HG-induced barrier damage using an in vitro model of human BBB comprising human brain microvascular endothelial cells (HBMEC) and astrocytes. Hyperglycemia (25 mmol/L D-glucose) markedly increased RhoA/Rho-kinase protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…showed that PKC-β and PKC-β II in human BMECs were activated after exposure to high glucose in an in vitro BBB model, and the activated PKC inhibited the expression of Occludin and undermined the integrity of BBB. Similar result was confirmed by transfecting BMECs with siRNA targeting PKC-β, in which the activation of PKC-β was impeded and the BBB damage was mitigated [35]. A recent study demonstrated that Go6983 decreased the phosphorylation levels of PKCδ and inhibited the release of MMP-9, which suggested that PKC-δ participated in PAR1-mediated MMP-9 release from pericytes, which lead to BBB dysfunction [40].…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 59%
See 1 more Smart Citation
“…showed that PKC-β and PKC-β II in human BMECs were activated after exposure to high glucose in an in vitro BBB model, and the activated PKC inhibited the expression of Occludin and undermined the integrity of BBB. Similar result was confirmed by transfecting BMECs with siRNA targeting PKC-β, in which the activation of PKC-β was impeded and the BBB damage was mitigated [35]. A recent study demonstrated that Go6983 decreased the phosphorylation levels of PKCδ and inhibited the release of MMP-9, which suggested that PKC-δ participated in PAR1-mediated MMP-9 release from pericytes, which lead to BBB dysfunction [40].…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 59%
“…Previous studies have confirmed that the activation of PKC is the major factor in CIRI [5,8,[35][36][37][38]. As previously reported, hypoxia-induced BBB permeability changes occur via a Cellular Physiology and Biochemistry…”
Section: Discussionmentioning
confidence: 49%
“…The protein levels of FAK, p63 (4A4), MMP1, MMP2, BrdU (Santacruz Biotech), Src, pFAK-Y 395 , MMP14 (Abcam), paxillin (BD biosciences), pPaxillin-Y 118 , pFAK-Y 576/577 , pSrc-Y 496 , pAKT-S 493 , total AKT, p-c-jun-S 73 , c-Jun (Cell Signaling) and β-actin (Sigma-aldrich) were detected in whole cell lysates by immunoblotting as previously described [50]. …”
Section: Methodsmentioning
confidence: 99%
“…PKCβ, in particular, quickly increases the RhoA/myosin-regulated light chain 2 pathway leading to increased brain edema following stroke [80]. Some isoforms are unable to translocate following ischemic injury and trigger intracellular pathways that contribute to neuronal death or injury [81].…”
Section: Pkc and Strokementioning
confidence: 99%